ORGANIZATIONAL FOUNDATIONS FOR THE ESTABLISHMENT OF PEDAGOGICAL COLLEGES OF THE SOVIET UKRAINE (1920-1925) - Vitraniuk, Nataliya O. (Educological discourse, 2016)
The article deals with the organizational bases of the formation of pedagogical technical schools as one of the types of educational establishments in the system of higher education of Ukraine in the 20s of the XX century. The Code of laws on public education (1922) with the type of higher educational institution in question is analysed. The comparative correlation of the activity of higher three-year pedagogical courses which were transformed into pedagogical technical schools, the requirements as to the organization of the teaching process in technical schools and higher three-year pedagogical courses, and the entrance conditions and organization of the teaching process in both types of educational establishments is carried out. The documentary proof of the stages of the formation of pedagogical technical schools till 1925 is revealed.